Analisa Hukum Terhadap Pemanfaatan Logam Tanah Jarang Berdasarkan UU No. 3 Tahun 2020 Tentang Perubahan Atas Undang-Undang No. 4 Tahun 2009 Tentang Pertambangan Mineral dan Batubara JO. PP No. 96 Tahun 2021 Tentang Pelaksanaan Kegiatan Usaha Pertambangan - Muhammad Haris Budi Agung (UNES Law Review, 2023)
The management and utilization of rare earth elements (REEs) have not been comprehensively regulated in the existing national legislation. Nevertheless, an analysis of Law No. 3 of 2020, which amends Law No. 4 of 2009 on Mineral and Coal Mining, suggests that the management of REEs is carried out within the framework of downstream mining policies that focus on increasing the value-added to raw materials, including purification processes before distribution to the market can be done. Government Regulation No. 96 of 2021 on the Implementation of Mineral and Coal Mining recognizes that rare earth metal elements such as monazite and xenotime are part of metallic minerals, and the obligation for processing and/or purification of REEs is outlined in the Minister of Energy and Mineral Resources Regulation No. 25 of 2018. even though the existence of LTJ has a strategic role in providing industrial and defense needs in the future. The currently very limited management and utilization policy for REEs in the country is contradictory to the latest sea sand sedimentation management policy contained in Government Regulation Number 26 of 2023 because it implies that there is an opportunity to export sea sand and its derivative products without prioritizing the conservation aspect of REEs. Regarding the relevant authority, the management and utilization of REEs also involve two central ministries, namely the Ministry of Energy and Mineral Resources and the Ministry of Industry, in order to create an effective and optimal roadmap for REEs management and utilisation in line with national interests.